Increasing Biodiversity and Land-Use Efficiency Through Pea (Pisum aestivum)-Canola (Brassica napus) Intercropping (Peaola) - Madsen, Isaac J.; Parks, Janice M.; Friesen, Maren L.; Clark, Robert E. (Frontiers in Soil Science, 2022)
Intercropping is an ancient agricultural management practice quickly re-gaining interest in mechanized agricultural systems. Mechanized management practices have led to decreased biodiversity at the macro and micro fauna levels. These agricultural practices have also resulted in the degradation of soil and long-term inefficiencies in land, water, and nutrients. The inland Pacific Northwest (iPNW) of the United States of America is a wheat dominated cropping system. The integration of winter and spring legumes and oilseeds has improved the biodiversity and nutrient use efficiency of the cropping systems. This paper examines the feasibility of pea-canola (peaola) intercropping in dryland production systems of the iPNW. In two site years, small plot peaola trials were established near Davenport, WA. Overall, the land equivalence ratio (LER) of peaola was found to be 1.46, showing an increase in efficiency of the system. Increasing N fertilizer application rates did not affect peaola yield, indicating that peaola has low demand for N inputs. The effects of peaola on insects and bacterial diversity were examined on replicated large scale strip trials. Peaola was found to have significantly greater numbers of beneficial insects than the monoculture controls. There were no significant differences between the diversity of the soil bacterial communities found in peaola versus pea and canola monocultures. However, we found that the strict core soil bacterial microbiome of peaola was larger than the monocultures and included core members from both the canola and pea soil microbiomes. In conclusion, the widespread adoption of peaola would likely increase biodiversity and increase use efficiency of dryland production systems in the iPNW.